(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
Marriage is a physical and mental bond or the existence of a legal relationship between husband and wife with the aim of forming a sakinah, mawaddah and rahmah household life based on the One Godhead. In terms of household objectives, it is not easy to maintain, if there have been continuous disputes resulting in divorce. The main issues discussed in this thesis are how the causes of divorce and how to consider the Judgment of the Religious Court of Maros Number: 7 / Pdt.G / 2021 / PA.Mrs regarding divorce divorce talak. To answer the main problem, research with empirical law type was carried out. The nature of the research used was analyzed qualitatively and then described in a descriptive manner, which was intended to obtain a clear and directed picture in order to answer the problem under study. The conclusion from the analysis is that the judge decision is in accordance with Article 116 of the Compilation of Islamic Law regarding the reasons for divorce in letter (f) between husband and wife where there are continuous disputes and quarrels and there is no hope of living in harmony again in the household, and the Judge decides cases are Verstek in Article 149 Paragraph (1) / Article 125 HIR. Abstrak Perkawinan adalah ikatan lahir bathin atau adanya hubungan hukum antara suami dan isteri dengan adanya tujuan untuk membentuk kehidupan rumah tangga yang sakinah, mawaddah dan rahmah berdasarkan Ketuhanan Yang Maha Esa. Dalam tujuan rumah tangga tidak mudah untuk mempertahankan, apabila telah terjadi perselisihan terus menerus yang mengakibatkan terjadinya perceraian. Pokok permasalahan yang dibahas dalam skripsi ini adalah bagaimanakah sebab-sebab terjadinya Perceraian dan Bagaimana Pertimbangan Putusan Hakum Pengadilan Agama Maros Nomor: 7/Pdt.G/2021/PA.Mrs tentang Perceraian cerai talak. Untuk menjawab pokok permasalahan tersebut dilakukan penelitian dengan tipe hukum empiris, sifat penelitian yang digunakan dianalisis secara kualitatif selanjutnya di uraikan secara deskriptif hal yang dimaksudkan untuk memperoleh gambaran yang dapat dipahami secara jelas dan terarah guna menjawab permasalahan yang diteliti. Kesimpulan dari analisis bahwa putusan hakim sesuai dengan Pasal 116 Kompilasi Hukum Islam tentang alasan-alasan perceraian pada huruf (f) antara suami dan isteri terus menerus terjadi perselisishan dan pertengkaran dan tidak ada harapan akan hidup rukun lagi dalam rumah tangga, dan Hakim memutus perkara bersifat Verstek dalam Pasal 149 Ayat (1)/Pasal 125 HIR.